Penyelesaian Tindak Pidana Kekerasan Dalam Rumah Tangga Berdasarkan Restorative Justice oleh Kepolisian Sektor Kandis - Nadya, Irvani; Firdaus, Emilda; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The completion of the crime of domestic violence based restorative justice is a necessary settlement. Restorative justice considers that a crime is a violation of people and relationships between citizens. The violations create obligations. In restorative justice justice includes victims, offenders and community members in an attempt to put everything correctly. This type of research can be classified into types of juridical sociological research, because in this study the authors directly conduct research on locations or places studied in order to give a complete and clear picture of the problems examined. This research was conducted in the Police Sector Kandis, while population and sample of this research is the police chief, Assistant Investigator, perpetrators and victims of domestic violence. Source of data used are primary data and secondary data and data collection techniques used interviews, questionnaires, and literature study. From the results of this study concluded that, first, the completion of the crime of domestic violence based on restorative justice by police Kandis sector, namely: that the application of Restorative Justice model of criminal acts against cases of domestic violence by the police Kandis sector in the system have described the application of Restorative models Justice namely in the form of implementation of the Alternative Dispute Resolution (ADR) in dealing with the crime of domestic violence, where ADR is a manifestation and implementation of models of Restorative Justice. Second, obstacles in solving the crime of domestic violence based on restorative justice by police Kandis sector, namely: where parties who are victims of violence is difficult to be consulted to achieve consensus and difficult to compromise. And also the perpetrators feel better punished and put in jail than have to come to terms with the victim. Third, efforts are being made to overcome the obstacles in solving the crime of domestic violence based on restorative justice by police Kandis sectors namely: the role of the police is required in order to be a good mediator violence cases can be resolved by peaceful means. First author's suggestion Police should improve and maximize its performance in order to implement the protection of the rights of victims of domestic violence. Secondly, in overcoming barriers Party who are victims of violence is difficult to be consulted to achieve consensus and difficult to compromise. The third attempt was made, investigators or the police can provide insight to the victim or the perpetrator of the road that should be taken to resolve cases of domestic violence. Keywords: Settlement - a criminal offense - violence - domestic - restorative justice